Heavy metals and community structure of microorganism changes during livestock manure composting with inoculation of effective microorganisms - Zhou, Haibin; Shen, Yujun; Li, Ran; Meng, Haibo; Zhang, Xi; Wang, Jian; Cheng, Hongsheng; Dong, Shanshan; Song, Liqiu; Ding, Jingtao; Cheng, Qiongyi (International Journal of Agricultural and Biological Engineering, 2020)
Effective microorganisms (EM) is usually used in composting to improve the composting process. However, the effect of EM on heavy metals evolution was still unclear. This study was performed to illustrate the microbial community changes that occur during composting with the addition of EM and to determine the evolution of heavy metal speciation during this process. The requirement of harmlessness for pig manure was met after the addition of EM at a dosage of 0.5%, with a germination index of 96.42%. The bacterial and fungal diversity were both found to decrease during the composting process. Additionally, the bioavailability of Cu and Pb decreased significantly during composting. Significant correlations were observed between the microbial composition and the percentage of different heavy metals fractions; however, the mechanism responsible for this correlation requires further investigation. This study has the potential to contribute to control of heavy metal contamination during the process of recycling pig manure through the controlled addition of EM.Keywords: effective microorganisms, heavy metal, microbial communities, pig manure; compostingDOI: 10.25165/j.ijabe.20201306.5674Citation: Zhou H B, Shen Y J, Li R, Meng H B, Zhang X, Wang J, et al. Heavy metals and community structure of microorganism changes during livestock manure composting with inoculation of effective microorganisms. Int J Agric & Biol Eng, 2020; 13(6): 125–132.